Die Restitution des Ullstein-Verlags (1945-52) Remigration, Ränke, Rückgabe: Der steinige Weg einer Berliner Traditionsfirma - Berndt, Juliane (Europäisch-jüdische Studien - Beiträge, 2020)
European-Jewish Studies reflect the interdisciplinary network and competence of the new "Centre for Jewish Studies Berlin and Brandenburg". The Centre gathers together the most important institutions working on Jewish studies in the region - including the relevant universities and establishments in Berlin and Potsdam. The interdisciplinary character of the series places particular emphasis on the way in which history, the humanities and cultural science approach the subject, as well as on fundamental intellectual, political and religious questions that inspire Jewish life and thinking today, and have influenced it in the past. The CONTRIBUTIONS publish excellent monographs and anthologies on the entire spectrum of themes from Jewish studies. The series is peer-reviewed.